Letter from Charles Detoy to Arnold O. Beckman - Detoy, Charles (1954)
Call for Arnold O. Beckman to serve on the Los Angeles Air Pollution Committee, from the L.A. Chamber of Commerce president, Charles Detoy.
Keywords: California--Los Angeles; Air--Pollution